2021
DOI: 10.1016/j.anr.2021.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Development and Feasibility Test of a Mouth Contactless Breathing Exercise Solution Using Virtual Reality: A Randomized Crossover Trial

Abstract: The purpose of this study was to develop a novel mouth contactless breathing exercise solution based on virtual reality (VR), and to test its feasibility. Methods: We developed the Virtual Reality-based Breathing Exercise System (VR-BRES), a self-regulating biofeedback breathing exercise with gaming characteristics and a soft stretch sensor. The feasibility and efficacy of the VR-BRES prototype were investigated through a randomized crossover trial. Fifty healthy adults participated in the trial, and their res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…This finding aligns with assertions made by other scholars, as its distinctiveness correlates to the visualization of respiratory signals that offers respiratory feedback. This was also emphasized by Kang et al VR-based breathing exercise system, 39 which provides biofeedback through breathing signal visualization, such as the avatar rabbit jump. The importance of this biofeedback was also underscored in a prior study, which demonstrated that women with limited thoracic movement experienced notable changes in respiratory parameters when incorporating visual feedback of diaphragmatic motion through ultrasound imaging into their VR breathing exercise regimen.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…This finding aligns with assertions made by other scholars, as its distinctiveness correlates to the visualization of respiratory signals that offers respiratory feedback. This was also emphasized by Kang et al VR-based breathing exercise system, 39 which provides biofeedback through breathing signal visualization, such as the avatar rabbit jump. The importance of this biofeedback was also underscored in a prior study, which demonstrated that women with limited thoracic movement experienced notable changes in respiratory parameters when incorporating visual feedback of diaphragmatic motion through ultrasound imaging into their VR breathing exercise regimen.…”
Section: Discussionmentioning
confidence: 96%
“…All of the evaluated research consistently placed focus on these features. One of the studies, 39 compared the efficacy and usefulness of a VR breathing exercise system to conventional deep breathing exercises. The findings of their trial indicated that although individual variations in breathing function exist, the use of a VR-based exercise system resulted in a noteworthy enhancement of breathing parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can benefit new nursing interns who may be afraid of occupational exposure events during practice-based learning. During clinical application, a VR system not only brings convenience to staff, but also actively and effectively interferes with patients' physical and mental health ( 27 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Penggunaan VR dan teknologi terkait telah berkembang dalam beberapa tahun terakhir karena manfaat sesuatu yang tidak diperoleh pada pendidikan klasik [10]. VR telah memberikan kontribusi penting bagi pendidikan karena memungkinkan peserta didik untuk memiliki pengalaman langsung terlibat dalam lingkungan atau situasi yang sulit untuk ditiru dalam pengajaran tradisional seperti ceramah, slideshows, atau video 2D [29] [31]. Selain itu, VR dapat menjadi alat belajar mandiri yang efektif dan memungkinkan guru memantau dan membimbing proses belajar siswa [10] [32].…”
Section: Kajian Literaturunclassified